Identification of a Key Amino Acid of the Human 5-HT2B Serotonin Receptor Important for Sarpogrelate Binding - Habib Abul Muntasir; Murad Hossain; Mohiuddin Ahmed Bhuiyan; Tadazumi Komiyama; Takashi Nakamura; Masanobu Ozaki; Takafumi Nagatomo (Journal of Pharmacological Sciences, 2007)
Based on radio-ligand binding and molecular modeling studies, sarpogrelate shows a moderate selectivity for 5-HT2B versus 5-HT2A receptors. To confirm the modeling data of sarpogrelate to 5-HT2B receptors predicting interaction of sarpogrelate towards Asp135 in helix 3 of 5-HT2B receptors, we constructed and characterized the mutation of this residue by site-directed mutagenesis. The Asp135Ala mutant did not exhibit any affinity for [3H]rauwolscine. Therefore, it was not possible to find sarpogrelate affinity to the mutant using [3H]rauwolscine. The mutation also abolished agonist-stimulated inositol phosphates formation. These results provide evidence that Asp135 is important for the interaction between 5-HT2B receptors and sarpogrelate. Keywords:: 5-HT2B receptor, sarpogrelate, site-directed mutagenesis